[Letter] Maseno, Kisumu, Kenya Colony [to Mr.] Hooper - Owen, Walter Edwin (Adam Matthew Digital, 1932)
Typescript letter from W.E. Owen, Archdeacon of Kavirondo, to H.D. Hooper. Includes commentary on the British administration's attitude towards land tenure and its potential impact on gold mining